Characterization of briquettes produced from eucalyptus wood waste generated in agro-industries - Sena, Andressa S.; Nahime, Bacus; Lima, Elton C.; Lobo, Fausto A.; Akasaki, Jorge L.; Santos, Igor S. dos (Revista brasileira de engenharia agrícola e ambiental, 2021)
ABSTRACT Boilers are widely used by industries and thermoelectric plants to generate renewable energy. However, when biomass is consumed, residues are generated, which for the most part cannot be discarded appropriately. This study investigated the reuse of eucalyptus wood waste with the goal of transforming the residue into resistant and durable briquettes for reuse in furnaces and boilers. The physico-chemical properties of the residue were studied in terms of chemical composition by X-ray fluorescence, and its crystalline structure was evaluated by X-ray diffraction. Both thermogravimetric analysis and differential thermogravimetric analysis were used to characterize the thermal decomposition of the wood waste residue. The residue was compacted in a universal press with sufficient humidity to fabricate briquettes under different conditions of mechanical pressure. Apparent density, durability, and burning tests were carried out on the briquettes. The maximum temperature reached during burning is dependent on the fabrication compaction pressure. The briquettes proved suitable for burning in boilers and furnaces, and their durability is advantageous for handling, reuse, and transportation. RESUMO Caldeiras são amplamente utilizadas por indústrias e usinas termelétricas para gerar energia renovável. Porém, quando a biomassa é consumida, resíduos são gerados, que em sua maioria não podem ser descartados de forma adequada. Este estudo investigou o reaproveitamento do resíduo de madeira de eucalipto com o objetivo de transforma-lo em briquetes resistentes e duráveis para reaproveitamento em fornos e caldeiras. As propriedades físico-químicas do resíduo foram estudadas em termos de composição química por fluorescência de raios-X, e sua estrutura cristalina foi avaliada por difração de raios-X. Ambas análises termogravimétrica e termogravimétrica diferencial foram utilizadas para caracterizar a decomposição térmica do resíduo de madeira. O resíduo foi compactado em prensa universal com umidade suficiente para a fabricação de briquetes sob diferentes condições de pressão mecânica. Os testes de densidade aparente, durabilidade e queima foram realizados nos briquetes. A temperatura máxima atingida durante a queima depende da pressão de compactação de fabricação. Os briquetes se mostraram adequados para queima em caldeiras e fornos, e sua durabilidade é vantajosa para manuseio, reutilização e transporte.